Pattern of Lower Gastrointestinal Diseases on Colonoscopy and Histopathological Examination in a Tertiary Care Center of Nepal - Roka, Kumar; KC, Indu; Jha, Sagar Mani; Subedi, Ram Chandra; Adhikari, Ayush (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: Many patients visiting the medicine outpatient department (OPD) and gastroenterology OPD have lower gastrointestinal (GI) symptoms and substantial would require to undergo colonoscopy. Colonoscopy is an effective endoscopic procedure to evaluate the entire colon from rectum to terminal ileum and perform some known therapeutic procedures. The aim of our study was to see the pattern of lower GI diseases in patients by colonoscopy and histopathological examination. Methods: This was a retrospective observational study conducted at Shree Birendra Hospital, Kathmandu, Nepal, after taking ethical approval from the Institutional Review Committee. Collective data of patients who underwent colonoscopy from October 2017 to September 2020 was evaluated from the endoscopy records. Analysis was done in the form of proportions and percentages and presented in tables and figures. Results: A total of 232 patients were evaluated. The most common indication was chronic abdominal pain 188 (81.03%) followed by per rectal bleeding 14 (6.03%) and chronic constipation 14 (6.03%). Colonoscopy showed normal findings in 182 (78.44%), colitis in 14 (6.03%), hemorrhoids and proctitis in 10 (4.31%) each, polyps in eight (3.44%), and malignancy in six (2.58%). Malignancy was proven in all six suspected patients by histopathological examination. Conclusions: Colonoscopy is an effective diagnostic modality for GI symptoms. Histopathological examination of the colonic biopsy showed a wide spectrum of common lower GI pathology from non-specific inflammation to malignancy with minimal complications. This shows colonoscopy as a safe and effective diagnostic modality for patients with lower gastrointestinal symptoms.